Pauline conversations in context : essays in honor of Calvin J. Roetzel - Roetzel, Calvin J.; Anderson, Janice Capel, 1952-; Sellew, Philip Harl; Setzer, Claudia (Journal for the study of the New Testament. Supplement series ;, 2002)
The conversations in this collection open by challenging ideas that have become standard and subject them to critical re-examination. The central thread of all these essays is a reflection on the processes of reading and theologizing. Among the contributors to this volume are David E. Aune, Jouette Bassler, Daniel Boyarin, Neil Elliott, Victor Paul Furnish, Lloyd Gaston, Steven J. Kraftchick, Robert C. Morgan, J. Andrew Overman, Mark Reasoner, Peter Richardson, and Robin Scroggs. Juanita Garciagodoy and David H. Hopper offer appreciations of Calvin Roetzel as a teacher and colleague.